Economic and Political Views of Madhav Sadashivrao Golwalkar - TAMTA, DR. SEEMA (The journal of contemporary issues in business and government, 2021)
Since ancient times, India has had a rich heritage of social and philosophical thinking. Indian political thoughts and thinkers have contributed significantly to the domains of World Politics, Sociology and Political Science. Who can ignore the noteworthy contribution of Kautilya in the realms of Diplomacy and Political Science? From Kautilya to Swami Vivekananda to Mahatma Gandhi, Sri Aurobindo, Rabindra Nath Tagore, Dr. Bheem Rao Ambedkar, Dr. Ram Mahohar Lohiya and more, the list is quite long. They represent a culture of diverse political thoughts existing in India at the same time. However, there are few thinkers whose political and social thoughts, despite being relevant, could not get a place in the syllabus of Indian Political Thought as a subject, perhaps due to political reasons. The name of Madhav Sadashivrao Golwalkar is one among such names. The second Sarsanghchalak of Rashtriya Swayamsevak Sangh is known for focusing on Swadeshi and linking the same to the economy of the country. He also promoted an economic system based on Swadeshi instead of capitalism and communism. In the light of present times, when the entire world is looking for a way out of the brunt caused by Covid-19, the political and economic thoughts of Golwalkar show a sustainable way to boost economies. This article focuses on the political and economic thoughts of Golwalkar.